Polyarticular Septic Arthritis From Streptococcus pneumoniae Infection in an Immunocompetent Adult: A Case Report - Kayley Xu; Matthew Wong-Pack; Ahraaz Wyne (Annals of Internal Medicine: Clinical Cases)
Polyarticular septic arthritis is a condition with significant morbidity and mortality that is rarely seen in immunocompetent adults. We report a case of a 73-year-old man presenting with a 2-day history of polyarthralgia involving bilateral shoulders, elbows, wrists, knees, and ankles with rigours and chills, initially treated as reactive arthritis and subsequently found to have Streptococcus pneumoniae bacteremia. Bilateral knee aspirations were performed for worsening arthritis despite antibiotics, revealing polyarticular septic arthritis that required bilateral arthroscopic washouts. This case illustrates the diagnostic challenges surrounding polyarticular septic arthritis and emphasizes the importance of timely recognition and treatment.